Impact of Sport Dance on Physical Fitness and Condition in the Opinion of Dancers from [N] Club in [City] - Warot, Julia; Zukow, Walery (Journal of Education, Health and Sport, 2025)
Background: Sport dance is a discipline that merges artistic expression with intense physical activity. It engages various motor abilities and may significantly influence physical fitness and conditioning. Despite its growing popularity, the physiological impact of dance training on the human body remains under-researched. Aim: The primary aim of this study was to assess the impact of regular sport dance training on dancers’ physical fitness and condition, as perceived by active participants in a dance club. Methods: A diagnostic survey method was employed to collect empirical data. The study used a self-constructed questionnaire as the primary research tool. Participants were asked to evaluate how sport dance training influenced their strength, flexibility, coordination, endurance, and general well-being. The main research question was supported by several specific sub-questions related to dance style, training elements, and observed physiological changes. Results: Findings revealed that regular sport dance training positively affects all major components of physical fitness. Standard dance styles were found to predominantly enhance endurance, while Latin dances were more effective in developing coordination. Notable improvements in physical condition were reported after a minimum of six months of consistent training. Additionally, participants cited various health benefits such as improved posture, reduced stress levels, and enhanced overall well-being. Conclusions: Sport dance exerts a multidimensional influence on physical fitness and conditioning. Key contributing factors include the frequency of training and the diversity of dance styles. It is essential to tailor training intensity to the dancer’s experience level and individual capacity. The study highlights the importance of continued research on the physiological and health-related impacts of sport dance, particularly across different age and experience groups.